PENGARUH QUALITY OF WORK-LIFE, MOTIVASI KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN MCDONALD’S’S, JAKARTA BARAT - Izzah Harista; Priehadi Dhasa Eka (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The purpose of this study is to examine the influence of quality of work-life, work motivation, and job satisfaction simultaneously on employee performance at McDonald’s’s. The research employs a quantitative approach with an associative method. The sample consists of 71 employees, selected using a total sampling or saturated sampling technique. Data analysis includes validity testing, reliability testing, classical assumption testing, correlation coefficient, coefficient of determination, t-test, and F-test. The findings indicate that quality of work-life has a significant effect on employee performance at McDonald’s’s, as evidenced by the result of t-count (6.779) > t-table (1.995), meaning hypothesis H1 is accepted. The correlation coefficient is 0.632, which falls into the strong category, with a contribution of 40%. The linear regression equation is Y=20.097+0.329X1, meaning that each one-point increase in quality of work-life will improve employee performance by 0.329 points. Furthermore, work motivation also has a significant effect on employee performance, as shown by t-count (6.154) > t-table (1.995), meaning hypothesis H2 is accepted. The correlation coefficient is 0.595, which falls into the moderate category, with a contribution of 35.4%. The linear regression equation is Y=24.260+0.719X2, meaning that each one-point increase in work motivation will improve employee performance by 0.719 points. Job satisfaction likewise has a significant effect on employee performance, as indicated by t-count (8.114) > t-table (1.995), meaning hypothesis H3 is accepted. The correlation coefficient is 0.699, which falls into the strong category, with a contribution of 48.8%. The linear regression equation is Y=22.067+0.485X3, meaning that each one-point increase in job satisfaction will improve employee performance by 0.485 points. Finally, quality of work-life, work motivation, and job satisfaction together have a significant effect on employee performance at McDonald’s’s, as evidenced by F-count (37.655) > F-table (2.742), meaning hypothesis H4 is accepted. The coefficient of determination shows that the three variables collectively explain 62.8% of the variance in employee performance. The linear regression equation is Y=12.787+0.140X1+0.290X2+0.312X3. The managerial implications of these findings emphasize the need for management to integrate human resource policies holistically. The synergy of these three variables forms a strategic foundation for an organizational culture oriented toward quality service, thereby not only enhancing individual productivity but also strengthening McDonald’s’s competitive advantage in the fast-food industry.